2020
DOI: 10.1200/jco.2020.38.15_suppl.10535
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II study of eribulin mesilate (ERI) plus irinotecan (IRI) in children with refractory or recurrent solid tumors.

Abstract: 10535 Background: ERI is an inhibitor of microtubule dynamics. IRI is used to treat pediatric sarcomas. In the pediatric preclinical testing program, ERI was well tolerated and had promising activity compared with vincristine (a common chemotherapeutic for pediatric cancers) for various solid tumors ( in vivo xenograft panels). Methods: Children with relapsed/refractory solid tumors (excluding active central nervous system tumors) were enrolled. Prior treatment with IRI was allowed. Dose escalation was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There is an ongoing phase 2 study evaluating eribulin which includes pediatric patients with relapsed or refractory RMS (NCT03441360). Eribulin was also studied in combination with irinotecan in a phase 1/2 trial of children with relapsed or refractory solid tumors [ 103 ]. The results from the phase 1 portion of the study were recently reported [ 103 ].…”
Section: Novel Cytotoxic Agents: Eribulinmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an ongoing phase 2 study evaluating eribulin which includes pediatric patients with relapsed or refractory RMS (NCT03441360). Eribulin was also studied in combination with irinotecan in a phase 1/2 trial of children with relapsed or refractory solid tumors [ 103 ]. The results from the phase 1 portion of the study were recently reported [ 103 ].…”
Section: Novel Cytotoxic Agents: Eribulinmentioning
confidence: 99%
“…Eribulin was also studied in combination with irinotecan in a phase 1/2 trial of children with relapsed or refractory solid tumors [ 103 ]. The results from the phase 1 portion of the study were recently reported [ 103 ]. There were 13 patients enrolled including four individuals with RMS.…”
Section: Novel Cytotoxic Agents: Eribulinmentioning
confidence: 99%
See 1 more Smart Citation